FACTORS AFFECTING MANAGEMENT INFORMATION SYSTEMS: SOFTWARE, DATABASES AND INFORMATION TECHNOLOGY (LITERATURE REVIEW) - Ali Marzuki Zebua; Kemas Imron Rosadi; Ulil Azmi (Dinasti International Journal of Education Management And Social Science, 2022)
Management Information System (MIS) is one of the most important achievements in the field of work administration, which aims to provide reliable, accurate, relevant and complete information to managers to improve organizational performance in organizations. This research reviews other research in the field of MIS adoption in organizations. Synthesizing from the previous literature with several books, articles and related studies, this paper proposes a theoretical framework. Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence Information Systems in the academic field, namely: Software, Databases and Information Technology, a literature study on Information Systems Management. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Software has an effect on Information Systems; 2) Database affects the Information System; and 3) Information Technology has an effect on Information Systems.